the Gaya Tokusatsu Pada Komik Islami Berjudul Ultimate Glad - hamdanu, Ayyub HBN; Dena Naufa Nabilla; Santi Widiastuti (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Tokusatsu is one of the popular Japanese culture in the world, including in Indonesia. This research is a Tokusatsu style analysis research on an Islamic themed comic entitled Ultimate Glad. This study was conducted to find out why the Ultimate Glad comic chose the Tokusatsu style to be combined with the Islamic theme, and to find out whether there are advantages and disadvantages of the Tokusatsu style combined in the Islamic comic entitled Ultimate Glad. This study uses a descriptive qualitative research method with data sources obtained from interviews with the publishers of Ultimate Glad comics, documentation, and testimonials from readers of Ultimate Glad comics. From this research, it can be benefited that the Tokusatsu style from Japan can be combined well with other themes, including Islamic themes, even with methods that are not easy.